Communication Style Organizasaun Lospalos Uan Ukani Members Student in Bandung - Felisianus Efrem Jelahut; Siti Karlinah; Evi Novianti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
This study aimed to reveal the communication styles in the Organizasaun Lospalos Uan Ukani Bandung organization with the influence of their original culture, namely Fataluku. This study uses a qualitative research method with a case study approach. The data sources in this study were divided into two types of data sources, namely primary sources and secondary sources. The technique of determining the informants in this study was using purposive sampling technique. The result showed that the communication style of the students of the Lospalos Uan Ukani Bandung members takes place with a formal communication style using the very standard Fataluku language. The speaking style of the members also used a verbal communication style by using words in speaking accompanied by non-verbal communication in the form of hand movements and facial mimics.